Effects of Collateral Status on Infarct Distribution Following Endovascular Therapy in Large Vessel Occlusion Stroke. Issue 9 (September 2020) - Al-Dasuqi, Khalid; Payabvash, Seyedmehdi; Torres-Flores, Gerardo A.; Strander, Sumita M.; Nguyen, Cindy Khanh; Peshwe, Krithika U.; Kodali, Sreeja; Silverman, Andrew; Malhotra, Ajay; Johnson, Michele H.; Matouk, Charles C.; Schindler, Joseph L.; et al.
Abstract : Background and Purpose: We aim to examine effects of collateral status and post-thrombectomy reperfusion on final infarct distribution and early functional outcome in patients with anterior circulation large vessel occlusion ischemic stroke. Methods: Patients with large vessel occlusion who underwent endovascular intervention were included in this study. All patients had baseline computed tomography angiography and follow-up magnetic resonance imaging. Collateral status was graded according to the criteria proposed by Miteff et al and reperfusion was assessed using the modified Thrombolysis in Cerebral Infarction (mTICI) system. We applied a multivariate voxel-wise general linear model to correlate the distribution of final infarction with collateral status and degree of reperfusion. Early favorable outcome was defined as a discharge modified Rankin Scale score ⩽2. Results: Of the 283 patients included, 129 (46%) had good, 97 (34%) had moderate, and 57 (20%) had poor collateral status. Successful reperfusion (mTICI 2b/3) was achieved in 206 (73%) patients. Poor collateral status was associated with infarction of middle cerebral artery border zones, whereas worse reperfusion (mTICI scores 0–2a) was associated with infarction of middle cerebral artery territory deep white matter tracts and the posterior limb of the internal capsule. In multivariate regression models, both mTICI ( P <0.001) and collateral status ( P <0.001) were among independent predictors of final infarct volumes. However, mTICI ( P <0.001), but not collateral status ( P =0.058), predicted favorable outcome at discharge. Conclusions: In this cohort of patients with large vessel occlusion stroke, both the collateral status and endovascular reperfusion were strongly associated with middle cerebral artery territory final infarct volumes. Our findings suggesting that baseline collateral status predominantly affected middle cerebral artery border zones infarction, whereas higher mTICI preserved deep white matter and internal capsule from infarction; may explain why reperfusion success—but not collateral status—was among the independent predictors of favorable outcome at discharge. Infarction of the lentiform nuclei was observed regardless of collateral status or reperfusion success. Abstract : Supplemental Digital Content is available in the text.